Association of Cerebral Small Vessel Disease Burden and Health-Related Quality of Life after Acute Ischemic Stroke - Liang, Yan; Chen, Yang-Kun; Deng, Min; Mok, Vincent C. T.; Wang, De-Feng; Ungvari, Gabor S.; Chu, Chiu-wing W.; Kamiya, Akane; Tang, Wai-Kwong (Frontiers in Aging Neuroscience, 2017)
Objective: Cerebral small vessel disease (SVD) is associated with increased mortality, disability and cognitive decline, depression in stroke survivors. This study examined the association between SVD burden, defined by a combination of SVD markers, and health-related quality of life (HRQoL) in acute ischemic stroke. Methods: Patients admitted with acute ischemic stroke of any etiology were prospectively screened between January 2010 to December 2014 and enrolled in the study if they met study entry criteria. HRQoL was evaluated with the 12-item Stroke Specific Quality of Life (SSQoL) at 3 months after the onset of acute ischemic stroke. SVD was ascertained by the presence of any of the SVD markers including lacune, white matter hyperintensities (WMH), cerebral microbleeds (CMB) and enlarged perivascular spaces (EPVS) in the basal ganglia or their combinations on brain magnetic resonance imaging (MRI). The presence of each individual marker scored 1 point and was summed up to generate an ordinal “SVD score” (0–4) capturing total SVD burden. Linear regression was used to determine the associations between SVD burden and HRQoL. Results: Of the743 acute ischemic stroke patients that formed he study sample (mean age: 66.3 ± 10.6 years; 41.7% women), 49.3%, 22.5%, 16.0%, 9.2% and 3.1% had SVD scores of 0, 1, 2, 3 and 4, respectively. After adjusting for demographic, clinical and imaging variables, the SVD score was independently associated with lower overall score of SSQoL (B = −1.39, SE = 0.56, p = 0.01), and its domains of mobility (B = −0.41, SE = 0.10, p < 0.001) and vision (B = −0.12, SE = 0.06, p = 0.03). Acute infract volume (B = −1.44, SE = 0.54, p = 0.01), functional independence (B = 5.69, SE = 0.34, p < 0.001) and anxious (B = −1.13, SE = 0.23, p < 0.001) and depressive symptoms (B = −3.41, SE = 0.22, p < 0.001) were also the significant predictors of the overall score of SSQoL. Conclusion: The brain’s SVD burden predicts lower HRQoL, predominantly in domains of mobility and vision at 3 months after acute ischemic stroke. The evaluation of SVD burden could facilitate developing individual treatment strategies.